Mapping quantitative trait loci of Meloidogyne graminicola resistance and tolerance in a recombinant inbred line population of Oryza glaberrima × O. sativa - Lawilao, Judith Galeng; Swamy, B.P. Mallikarjuna; Kumar, Arvind; Cabasan, Ma. Teodora Nadong; De Waele, Dirk (Brill, 2019)
Host response of BC2F3 recombinant inbred line (RIL) population derived from a cross between African rice (CG14) and Asian rice (IR64) genotypes was evaluated in the field and quantitative trait loci (QTLs) that confer resistance and tolerance to Meloidogyne graminicola were mapped using SSR markers. Of the 155 BC2F3 progenies evaluated, 23 were resistant and six were partially resistant based on the number of second-stage juveniles (J2) per root system and J2 per g roots. Based on yield reduction, 23 progenies were identified as tolerant and 14 were less sensitive to M. graminicola infection. QTLs related to resistance were detected on chromosomes 6, 7 and 12. QTL for tolerance linked to percentage yield reduction was mapped on chromosome 5. QTLs linked to fresh root weight, dry root weight, dry shoot weight, percentage filled grains per panicle and yields were also mapped. QTLs identified will be useful in a breeding programme to develop M. graminicola-resistant and tolerant rice cultivars.